PENERAPAN METODA SIX SIGMA DENGAN PENDEKATAN DMAIC UNTUK MENGURANGI BIAYA KEGAGALAN INTERNAL PADA PRODUKSI KANTONG SEMEN PASTED BAG DI PABRIK KANTONG PT. SEMEN PADANG - Gamindra Jauhari (Sekolah Tinggi Teknologi Industri Padang, 2016)
Cement Bags Division at PT. Semen Padang in Padang has an important division to produce a number of problem. Bags produced of two types, including sewing bag and pasted bag. Quality problems or quality in production has always been a complex problem in the process of production. The tolerance limit of 1.2% the company but many defects that over range becomes a major problem because over cost quality. This research was done because of the quality problems at the cement bags division PT. Semen Padang. This purpose study was to apply the Six Sigma method in reduce product defects.The result of applying six sigma calculate internal failure costs. Data processing and analysis techniques used in this study is the six sigma method (define, measure, analysis, improve and control). In the calculation capability sigma and DPMO (Defect per million opportunites) using six sigma calculator. The results of this study showed that based on calculations using six sigma method with the DMAIC approach (define, measure, analyze, improve and control) can reduce product defects and internal failure costs caused by the defective product. Key Words: Six Sigma, DMAIC, Defect Products, Failure Costs.